The Empirical Study on the Impact of the COVID-19 on Small and Medium Enterprises (SMEs) in Bangladesh - Rahman, Md. Motiur; Bhuiyan, Mohammad Rakibul Islam; Alam, S. M. Ashraful (Journal of Information System and Informatics, 2024)
The large COVID-19 disease outbreak had a devastating impact on the entire world, with Bangladesh being one of the worst-affected nations. The epidemic worsened the situation of small and medium-sized companies (SMEs) in Bangladesh. The goal of this study is to examine the possibilities and difficulties faced by SMEs in Bangladesh's Rangpur district during the COVID-19 epidemic and the transition to the new normal. The research methodology combines an exploratory technique with a quantitative methodology. The study is designed on both primary and secondary data. Researchers collected data from 290 respondents from Rangpur District. The first finding of the study is that the most significant proportion of business is small enterprise which is 83.4 percentage. Lack of opportunities and business scope, there are less numbers of medium enterprise in the Rangpur district that is around 17%. Second one, opportunity of COVID-19, around 71% businesses have been improved financial condition by working capital in pandemic situation which is one the opportunity for SMEs. Moreover, commerce increase which is 40% of the respondents. Technological adaptation and E-commerce are the positive sides for improving socio-economic development for Rangpur district. challenge’soint of challenges view, COVID-19 on SMEs is the largest competition between business which is approximately 72% and total responses is 209 out of 290.